Comparison of ferric carboxymaltose and iron sucrose for treatment of iron deficiency anemia in pregnancy at tertiary care centre, Western India - Papaniya, Twinkle D.; Parmar, Mehul T.; Solanki, Harsha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Iron deficiency anemia is the most common haematological health problem among pregnant women but can be prevented by effective measure. The study aimed to evaluate the efficacy and safety of intravenous ferric carboxymaltose (FCM) in comparison with intravenous Iron sucrose (IS) for treatment of iron deficiency anemia in pregnancy. Methods: A prospective interventional comparative study was conducted from (June 2021-June 2022) at a tertiary care hospital. Pregnant women diagnosed with moderate to severe iron deficiency anaemia were screened for the study. One hundred patients were randomized to receive either intravenous FCM or IS. Treatment effectiveness was assessed by repeat Haemoglobin (Hb) and RBC indices measurement after 4 weeks of completion of therapy. Safety was assessed by analysis of adverse drug reactions during infusion and 2 hours after infusion. Results: Mean rise in Hb at 4 weeks was significantly higher in FCM group (1.67±0.47 Vs 1.07±0.25; p<0.0001) as compared to IS group. There was also rise in other biochemical parameters like MCV and MCHC in both groups. Numbers of visits were significantly less in FCM group. No serious adverse events were noted in either group. Conclusions: Intravenous ferric carboxymaltose is more effective and safer as compared to intravenous iron sucrose in the management of anemia during pregnancy. It has advantage to administer large dose in single sitting which reduce overall cost of therapy and hence will lead to better compliance in community setting.